2019
DOI: 10.1111/nmo.13679
|View full text |Cite
|
Sign up to set email alerts
|

The international anorectal physiology working group (IAPWG) recommendations: Standardized testing protocol and the London classification for disorders of anorectal function

Abstract: BackgroundThis manuscript summarizes consensus reached by the International Anorectal Physiology Working Group (IAPWG) for the performance, terminology used, and interpretation of anorectal function testing including anorectal manometry (focused on high‐resolution manometry), the rectal sensory test, and the balloon expulsion test. Based on these measurements, a classification system for disorders of anorectal function is proposed.MethodsTwenty‐nine working group members (clinicians/academics in the field of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
242
1
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(308 citation statements)
references
References 32 publications
6
242
1
18
Order By: Relevance
“…Indeed, a 2019 consensus document recommends that manometry "should be performed in the left lateral position." 18 During evacuation, the default ManoScan™ (Medtronic Inc, Minneapolis, MN) software algorithm for analyzing HRM identifies the highest rectoanal gradient (RAG) over a consecutive period of 2 seconds during the 20-second maneuver. (We use a duration of 3 seconds, which is arguably more representative of evacuation than the default ManoView™ option of 2 seconds.)…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a 2019 consensus document recommends that manometry "should be performed in the left lateral position." 18 During evacuation, the default ManoScan™ (Medtronic Inc, Minneapolis, MN) software algorithm for analyzing HRM identifies the highest rectoanal gradient (RAG) over a consecutive period of 2 seconds during the 20-second maneuver. (We use a duration of 3 seconds, which is arguably more representative of evacuation than the default ManoView™ option of 2 seconds.)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the left lateral decubitus position is recommended by The International Anorectal Physiology Working Group. 21 When it comes to treatment for DD, coaching has in one study revealed a normalization of manometric results in 12 out of 39 patients. 26 Type I DD was dominant in our patients with constipation, found in eight out of 13 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In patients ful lling the diagnostic criteria for functional chronic constipation, dyssynergic defecation (DD) was de ned according to the following diagnostic criteria which have shown to be in line with the London Classi cation. 20,21 1. Patients must demonstrate an obstructive pattern of defecation during high resolution anorectal manometry at more than one attempt…”
Section: Clinical Examinations 251 High Resolution Anorectal Manommentioning
confidence: 99%
“…The test provides information such as (1) voluntary and involuntary anal sphincter function including measurement of the resting and squeeze sphincter pressure, and the functional length of the anal canal, (2) rectoanal inhibitory reflex (RAIR) activity during rectal distension, (3) rectal sensation, (4) rectal compliance, and (5) evacuatory function. [2][3][4] Definitions of several of these measures along with others commonly used to describe anorectal physiology are provided in ►Table 1. 5 An ARM study requires four main equipment consisting of a probe, pressure recording device, device for displaying the recordings (e.g., monitor or printer), and a device for both data analysis and storage (e.g., computer or chart recorder).…”
Section: Physiologic Tests In Rectal Prolapse Anorectal Manometrymentioning
confidence: 99%
“…In some ARM protocols, a "cough" is also included between the "squeeze" and "push" phases to document the cough pressure. 3 Dyssynergic defecation occurs when a patient is unable to coordinate their abdominal and pelvic floor muscles to successfully evacuate stool 11 (►Fig. 2).…”
Section: Measure Definitionmentioning
confidence: 99%